Contribution Of Educational Psychology To The Development Of The Islamic Education Curriculum - Ardiansyah; Iskandar (Yayasan pendidikan dzurriyatul Quran, 2024)
Developing an Islamic education curriculum is important in improving the quality of Islamic education institutions. The aim of this research is to analyze and describe the contribution of educational psychology to the development of the Islamic education curriculum. The method in this research uses a library research approach. In this study there was no research location, because all data was taken from journals, books and scientific proceedings. The data collection technique in this research uses documentation, with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of this research can be described as showing that educational psychology has an important role in developing the Islamic education curriculum. The use of educational psychology principles in developing Islamic education curricula can help create an inclusive learning environment and support students' holistic growth. By integrating educational psychology concepts, the Islamic education curriculum can be adapted to current needs, including challenges and changes in the continuously developing educational environment. Educational psychology can also provide insight into how to motivate students and overcome barriers to learning in the context of Islamic education.